Bakery training improvement for diversification produtc at mamba'ul hikmah islamic boarding school cafe, kendal - Purnaningsih, Sri; Susanthi, Dethi; Hidayah, Muhammad Rizky Nur (Abdi Masya, 2025)
Products in a cafe, become something that is a mainstay and always sought after by consumers, so that the products of a business place are always sought after, there must always be something new and varied, especially in the cafe of the Mamba'ul Hikmah Islamic boarding school, Sabetan, Mororejo, Kaliwunggu, Kendal, Central Java. This community service aims to provide competence in making bakery products to students and male students in the Mamba'ul Hikmah Islamic boarding school environment. Community service is carried out through the survey and interview stages, opening and grouping students, followed by training in each activity group. Training in making standard bakery, weighing ingredients, mixing, stirring, fermentation 1, weighing, fermentation 2, forming, filling, fermentation 3, baking, and cooling. The bakery products trained were Gembong bread and Boy bread filled with butter totaling 47 portions. The number of participants in the bakery making training group was 10 people, consisting of 3 men and 7 women. The results obtained from this Community Service activity include: Students can make bakery products in the form of roti Boy and roti Gembong as product diversification. In general, training participants expressed satisfaction with this activity, which is 90%. This is proven by all participants being able to make bakery products in the form of roti Gembong and roti Boy correctly.